Evaluation of natural gas expansion as a bridge to energy transition in Brazil - Barbosa, Luciana Pereira; Moura, Lyzette Gonçalves Moraes de; Barros Filho, Allan Kardec Duailibe (Latin American Journal of Energy Research, 2024)
The objective of this article is to carry out an evaluation of the expansion of natural gas as a bridge to the low-carbon energy transition in terms of infrastructure, availability, consumption and production. The results achieved during the study could give the necessary focus on the issue of gas internalization, even knowing that the pipeline networks are located, mostly in the vicinity of the country's coast, since it is the region that has more industry. the other hand, this hinders access to this resource in central regions of the country by this modal, and it is necessary to enable other logistical forms that can contribute to the economic development of the states, especially the State of Maranhão, because it has a large amount of exploratory block, and this would add significantly to its economic development in the state. Therefore, strategies are needed to increase access to these natural gas resources.
Keywords: Natural Gas; Energy Transition; Interiorization; Natural Gas Infrastructure; Regional Economic Development